Pendidikan Karakter:Model Pembinaan Karakter Anak Oleh Guru-guru Sekolah Minggu - Simatauw, Marfy (Sekolah Tinggi Teologi Borneo, 2023)
Abstract: This journal article aims to analyze the pattern of character building for children carried out by Sunday school teachers in teaching children of this age to have a good personality from an early age and have good character and noble character in increasing faith in God. The importance of keeping this journal is due to problems in raising children in Sunday school related to bad children's characters such as; lack of politeness, not wanting to be regulated, stealing, uttering dirty words, in association with the community, this is a challenge for teachers in fostering children at school.The character development of children implemented by Sunday school teachers plays a very important role in educating children at an early age, because children at this age if nurtured properly and regularly can have very good impact changes such as; have good morals, be polite, love one another and fear God according to the word of God, II Timothy 3:16